Analisis Kinerja Pendistribusian Pakan Ternak dari Limbah Ikan Berdasarkan Model Performance of Activity (POA) dan Supply Chain Operation Reference 9.0 di UD. Ridwan - Arie Saputra; Nissa Prasanti; Trinaljo Sagala; Fitriadi Fitriadi (Universitas Teuku Umar, 2021)
UD.Ridwan is one of the community businesses in West Aceh, precisely in Ujong Kalak, which processes fish waste into animal feed. UD.Ridwan in its business activities has experienced several problems in the part of the supply of raw materials that are not fixed, because the amount of fish waste is not fixed per day. UD. RIDWAN in its production activities, every 1 kg of raw materials used can produce 761 grams of feed product. As a result, the results of feed production are also not fixed, and cannot fulfill orders from consumers, so there is often a mismatch between demand and orders. This will lead to unfulfilled consumer demand and delays in distribution to each distribution center (DC). UD. Ridwan distributes his products to existing DCs, namely: Medan, Banda Aceh, and Lhokseumawe. To fix the losses faced by the company, it is necessary to measure the performance of the supply chain first. There are several models of supply chain performance measurement systems, namely: POA (Performance of Activity) and SCOR (Supply Chain Operation Reference). POA is a model used to measure the performance of activities that are part of the process in the supply chain. Activity performance is measured in various dimensions, namely: costs, time, capacity, capabilities, productivity, utilization and outcomes. Meanwhile, SCOR is basically a model based on a process